Activation of endocytosis as an adaptation to the mammalian host by trypanosomes. - Natesan, S; Peacock, L; Matthews, K; Gibson, W; Field, M (2007)
Immune evasion in African trypanosomes is principally mediated by antigenic variation, but rapid internalization of surface-bound immune factors may contribute to survival. Endocytosis is upregulated approximately 10-fold in bloodstream compared to procyclic forms, and surface coat remodeling accompanies transition between these life stages. Here we examined expression of endocytosis markers in tsetse fly stages in vivo and monitored modulation during transition from bloodstream to procyclic forms in vitro. Among bloodstream stages nonproliferative stumpy forms have endocytic activity similar to that seen with rapidly dividing slender forms, while differentiation of stumpy forms to procyclic forms is accompanied by rapid down-regulation of Rab11 and clathrin, suggesting that modulation of endocytic and recycling systems accompanies this differentiation event. Significantly, rapid down-regulation of endocytic markers occurs upon entering the insect midgut and expression of Rab11 and clathrin remains low throughout subsequent development, which suggests that high endocytic activity is not required for remodeling the parasite surface or for survival within the fly. However, salivary gland metacyclic forms dramatically increase expression of clathrin and Rab11, indicating that emergence of mammalian infective forms is coupled to reacquisition of a high-activity endocytic-recycling system. These data suggest that high-level endocytosis in Trypanosoma brucei is an adaptation required for viability in the mammalian host.